2019
DOI: 10.4081/ejtm.2019.8354
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between ultrasonographic findings and fine needle aspiration cytology in differentiating malignant and benign thyroid nodules

Abstract: The purpose of research was comparing the ultrasound (US) features and fine-needle aspiration cytology (FNAC) in detecting the thyroid nodules in clinical practice. A cross-sectional analytical study retrospectively reviewed the US and FNAC findings for a total of 170 thyroid nodules. The US features that we compared included echogenicity, calcifications, shape, halo and Doppler, between 2017 and 2018. Totally, 170 nodules of thyroid were studied, which contained 72 (42.4%) benign and 98 (57.6%) malignant thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Arpana et al [14] USG features significantly associated with malignancy for thyroid lesions in his study; It has been reported that the size of the thyroid nodule is >30 mm, its borders are unclear, solid echotexture, hypoechoic lesion, microcalcification, and increased vascularity. Mohebbi et al [15] compared ultrasound features with fine needle aspiration cytology in the detection of thyroid nodules in clinical practice. Sonographic features such as microcalcification, hyper echogenicity, wider than elongated shape, no halo were found to be significantly associated with malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Arpana et al [14] USG features significantly associated with malignancy for thyroid lesions in his study; It has been reported that the size of the thyroid nodule is >30 mm, its borders are unclear, solid echotexture, hypoechoic lesion, microcalcification, and increased vascularity. Mohebbi et al [15] compared ultrasound features with fine needle aspiration cytology in the detection of thyroid nodules in clinical practice. Sonographic features such as microcalcification, hyper echogenicity, wider than elongated shape, no halo were found to be significantly associated with malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…The taller-than-wide shape (vertical) was significantly associated with malignancy [23]. Taller-than-wide nodules with microcalcifications were most likely to be malignant, and there was a strong negative correlation between the size and taller-than-wide shape of a thyroid nodule [24].…”
Section: Discussionmentioning
confidence: 99%
“…FNA should be used for planning surgery for thyroid nodules and especially for follow-up with the patients [ 4 ]. Detection of thyroid malignancies at early stages is being achieved by this treatment, which is becoming more common because of its simplicity, cheap cost, and lack of serious consequences.…”
Section: Introductionmentioning
confidence: 99%